The Oxford handbook of transformations of the state - Leibfried, Stephan 1944-2018; Huber, Evelyne 1950-; Lange, Matthew 1974-; Levy, Jonah D.; Nullmeier, Frank 1957-; Stephens, John D. 1947- (Oxford University Press, 2015)
This Handbook offers a comprehensive treatment of transformations of the state, from its origins in different parts of the world and different time periods to its transformations since World War II in the advanced industrial countries, the post-Communist world, and the Global South. 0Leading experts in their fields, from Europe and North America, discuss conceptualizations and theories of the state and the transformations of the state in its engagement with a changing international environment as well as with changing domestic economic, social, and political challenges. The Handbook covers different types of states in the Global South (from failed to predatory, rentier and developmental), in different kinds of advanced industrial political economies (corporatist, statist, liberal, import substitution industrialization), and in various post-Communist countries (Russia, China, successor states to the USSR, and Eastern Europe). It also addresses crucial challenges in different areas of state intervention, from security to financial regulation, migration, welfare states, democratization and quality of democracy, ethno-nationalism, and human development. 0The volume makes a compelling case that far from losing its relevance in the face of globalization, the state remains a key actor in all areas of social and economic life, changing its areas of intervention, its modes of operation, and its structures in adaption to new international and domestic challenges